New advances in immune mechanism and treatment during ocular toxoplasmosis - Chen, Zijian; Cheng, Shizhou; Chen, Xiaoming; Zhang, Zuhai; Du, Yanhua (Frontiers in Immunology, 2024)
Ocular toxoplasmosis (OT) is an intraocular infection caused by the parasite Toxoplasma gondii. OT is manifested as retinal choroiditis and is the most common infectious cause of posterior uveitis. Invasion of the retina by T. gondii leads to disruption of the blood-ocular barrier and promotes the migration of immune cells to the ocular tissues. Cytokines such as IFN-γ and IL-1β are effective for controlling parasite growth, but excessive inflammatory responses can cause damage to the host. In this review, we will discuss in detail the latest advances in the immunopathology and treatment of OT.